Assessment and reclamation of contaminated land - Hester, R. E.; Harrison, Roy M., 1948- (Issues in environmental science and technology ;, 2001)
Contaminated land and the methods and legal controls governing its reclamation for subsequent development and use are of great current interest and concern. This volume covers aspects of this subject, ranging from the origins and extent of contaminated land problems, including effects on human health, through investigative measures, to specific techniques of remediation. It is written in the context of the new UK contaminated land regime and includes human and ecological risk assessment methodology, and the legal liabilities and insurance aspects of contaminated land. This authoritative review will be welcomed by those involved in the areas of land use planning and development, consultants and engineers in contaminated site investigation and remediation, and environmental regulators. Students of land management and environmental science will also find it essential reading.